Efektifitas Penyuluhan Terhadap Pengetahuan Ibu Balita Tentang Menu Seimbang Balita Di Posyandu Melati Desa Muara Langsat Kuantan Singingi 2016 - Syafriani Syafriani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
Lack of knowledge about nutrition and health among parents, especially the mother is one of the causes of malnutrition in children under five. In the province of Riau in 2013 one of the highest malnutrition status is Regency Kuantan Singingi with a prevalence of 5.6%. There are malnourished children under five In the district of Kuantan Singingi, sentajo technical implementation unit area (UPTD) health sector, in the village of Muara Langsat with children malnutrition amounted to (0.9%) in 2015. The aim of this study was to determine the effectiveness of counseling to mothers knowledge about a balanced diet for children under five in posyandu of Melati  in the village of Muara Langsat Regency Kuantan Singingi year 2016. this study used a quasi experiment method non equivalent control group design. The data collection study conducted using questionnaires. The study population was 302 children under five. Sampling using purposive sampling obtained 256 children under five. The results showed an average score of knowledge (pretest) of 0.44 and an average knowledge (posttest) increased to 1.08. Results of paired t-test analysis, knowledge of mothers about balanced diets gained significant value ρ = 0.000 (ρ 0.05). This means that there is effective counseling to mothers knowledge about balanced menu for children under five. It is expected that health professionals, especially midwives in order to further improve public knowledge about the importance of eating a balanced diet in children under five like posyandu counseling, and so on.